2020
DOI: 10.1002/ana.25781
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Separation of Tremor and Ataxia in Essential Tremor

Abstract: Objective This study addresses an important problem in neurology, distinguishing tremor and ataxia using quantitative methods. Specifically, we aimed to quantitatively separate dysmetria, a cardinal sign of ataxia, from tremor in essential tremor (ET). Methods In Experiment 1, we compared 19 participants diagnosed with ET undergoing thalamic deep brain stimulation (DBS; ETDBS) to 19 healthy controls (HC). We quantified tremor during postural tasks using accelerometry and dysmetria with fast, reverse‐at‐target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Interestingly, stride length variability reduced to the level of HC, suggesting that VIM DBS may possibly have reduced the risk of falls for these subjects although our dataset did not have a validated measure of falls to compare. Consistent with previous studies [ 1 16 27 ], DBS was effective in reducing upper limb tremor. Here, we found reduction in upper limb tremor during an overground walking and postural balance task.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, stride length variability reduced to the level of HC, suggesting that VIM DBS may possibly have reduced the risk of falls for these subjects although our dataset did not have a validated measure of falls to compare. Consistent with previous studies [ 1 16 27 ], DBS was effective in reducing upper limb tremor. Here, we found reduction in upper limb tremor during an overground walking and postural balance task.…”
Section: Discussionsupporting
confidence: 91%
“…We quantified tremor during the postural balance task as the sum of power from 4–8 Hz in the middle 20 s of the raw acceleration signal during quiet standing for each wearable sensor (lumbar, sternum, left ankle, right ankle, left wrist, right wrist) [ 26 27 ]. To achieve this, we performed a power spectral analysis of the acceleration signal of the transverse, sagittal, and frontal planes for each body location ( Figure 1B ) using a customized MATLAB program (Math Works TM Inc., Natick, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in a wave-variable processor model where the cerebellum is assumed to contribute to the servo-motor mechanism, a reduction in cerebellar output results in large regular oscillations [86]. Furthermore, dysmetria and tremor are independent of each other in essential tremor [87].…”
Section: Poor Prediction and Compensatory Feedback Correctionsmentioning
confidence: 99%
“…Furthermore, the scoring criteria of BARS and the International Cooperative Ataxia Rating Scale (ICARS) [17] suggest that segmentation of movement increases with disease severity on the finger-to-nose test (FNT). Prior work has also demonstrated that information extracted from the FNT is related to the presence of ataxia and its severity [10,18,19].…”
Section: Introductionmentioning
confidence: 99%